Identification of ATRNL1 and WNT9A as novel key genes and drug candidates in hypertrophic cardiomyopathy: integrative bioinformatics and experimental validation - He, Huabin; Liao, Yanhui; Chen, Yang; Qin, Hao; Hu, Longlong; Xiao, Shucai; Wang, Huijian; Yang, Renqiang (Frontiers in Molecular Biosciences, 2024)
Background Hypertrophic cardiomyopathy (HCM) is a genetic disorder characterized by left ventricular hypertrophy that can lead to heart failure, arrhythmias, and sudden cardiac death. Despite extensive research, the molecular mechanisms underlying HCM are not fully understood, and effective treatments remain limited. By leveraging bioinformatics and experimental validation, this study aims to identify key genes and pathways involved in HCM, uncover novel drug candidates, and provide new insights into its pathogenesis and potential therapeutic strategies. Methods Commonly upregulated and downregulated genes in hypertrophic cardiomyopathy (HCM) were identified using Gene Expression Omnibus (GEO) datasets, including three mRNA profiling datasets and one miRNA expression dataset. Enrichment analysis and hub-gene exploration were performed using interaction networks and consistent miRNA-mRNA matches. Potential drugs for HCM were screened. HCM cellular and animal models were established using isoproterenol. Key unstudied differentially expressed genes (DEGs) were validated. Animals were treated with novel potential drugs, and improvements in HCM were assessed via ultrasound metrics. Hematoxylin and eosin (H&E) staining was used to assess myocardial fibrosis. Immunohistochemistry was employed to detect DEGs in cellular experiments. Result We discovered 145 key upregulated and 149 downregulated DEGs associated with HCM development, among which there are eight core upregulated and seven core downregulated genes. There are 30 upregulated and six downregulated miRNAs. Between the six downregulated miRNAs and 1291 matched miRNAs (against eight core upregulated DEGs), there is one common miRNA, miR-1469. Using the CTD database, drugs that impact the expression/abundance/methylation/metabolic process of core DEGs (after the exclusion of toxic drugs) included acetaminophen, propylthiouracil, methapyrilene, triptolide, tretinoin, etc. In the HCM cell model, only ATRNL1 and WNT9A were significantly increased. In the HCM animal model, propylthiouracil, miR-1469, and triptolide demonstrated varying degrees of therapeutic effects on HCM. Propylthiouracil, but not miR-1469 or triptolide, significantly inhibited the expression of ATRNL1 in the HCM model, and all three drugs suppressed WNT9A expression. Conclusion We identified several novel genes in HCM development, among which ATRNL1 and WNT9A were validated by cell and animal models. A deficiency of hsa-miR-1469 may be a mechanism behind HCM development. Novel medications for HCM treatment include propylthiouracil and triptolide.